Guidance for hypersonic re‐entry using receding horizon control with finite terminal weighting matrix. (27th April 2022) - Sun, Qichao; Xu, Juanjuan; Zhang, Huanshui
Abstract: In this article, nominal‐trajectory‐based guidance approach for hypersonic reentry vehicles is considered using the Vinh's equations. The nominal trajectory is generated via pseudo‐spectral method and then tracked by receding horizon control approach. Specially, several strategies are adopted to simplify the practical application. First, we formulate the receding optimal problem discretely using the approximated discrete linear state error dynamics. Thus, the differential matrix Riccati equation is substituted by a difference matrix Riccati equation. Second, we set the terminal state weighting matrix finite which brings flexibility of adjusting the sample period and prediction horizon. Third, the time‐varying state error dynamics is approximated by time invariant system. Lastly, instead of obtaining terminal weighting matrices which satisfy a linear matrix inequality using the LMI toolbox, we set them the same constant matrix. Naturally, numerical simulation is available to verify the validity and efficiency of the proposed approach.